New and additional records of hyperiidean amphipods of the infraorder Physosomata (Crustacea: Amphipoda: Hyperiidea) from the Antarctic Zone of the Southern Ocean - Zeidler, Wolfgang (Zootaxa, 2019)
New and additional records of hyperiidean amphipods of the infraorder Physosomata from the Antarctic Zone of the Southern Ocean, based on specimens in the USNM, are documented. They represent several range extensions for species previously recorded from the region as well as 14 new records with another three recorded from within a few degrees north of the Antarctic Zone. The following species represent new records for the Antarctic Zone: Lanceola loveni loveni, L. sphaerica, Megalanceoloides remipes, Microphasmoides vitjazi, Mimonecteola diomedeae, M. macronyx, Mimonectes diomedeae, M. loveni, Cheloscina antennula, Ctenoscina macropa, Scina curilensis, S. incerta, S. stebbingi and S. vosseleri. In addition, Lanceola felina, L. loveni grossipes and L. pacifica are recorded for the first time from the Southern Ocean, just 1°–3°N of the Antarctic Zone.